Comparison Of Liquid Luria Broth Media and Molasses Media on Recombinant L-Arabinose Isomerase Enzyme Production From Geobacillus Stearothermophilus - Maulida, Aulia; Puspitasari, Riris Lindiawati; Noriko, Nita (Universitas Al Azhar Indonesia, 2024)
L-Arabinose isomerase (L-AI) is a type of intracellular enzyme catalyzes the reversible isomerization reaction of L-arabinose to L-ribulose, besides that it can convert D-galactose to D-tagatose. One of the bacteria that can produce this enzyme is Geobacillus stearothermophilus. The high price of instant media, which reaches IDR 1,500,000 to IDR 3.000.000,- for every 500 g and the abundance of natural resources that can be used as a medium for the growth of microorganisms encourages researchers to find alternative media from materials that are easy to get and do not require expensive costs. The researchers compared the effectiveness of liquid Luria Broth (LB) media and molasses media for enzyme production. The research involved inoculating bacteria in both media types, followed by subculture and incubation. IPTG was added to induce enzyme production, followed by cell harvesting through centrifugation and sonication. Enzyme activity was evaluated using SDS PAGE and the cysteine carbazole method. Molasses showed promising results due to water solubility, enzyme activity, abundance, and cost-effectiveness. Molasses appears as an alternative with active enzymes, water solubility, abundant availability, and significant cost savings, making it a viable choice for enzyme production.Keywords— L- Arabinose Isomerase, Molasses, Enzyme